Hubungan Durasi Merokok Orang Tua dengan Kejadian ISPA pada Balita - Ridho Abdillah; Herry Susanto; Indra Tri Astuti; Indra Tri A (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Acute Respiratory Infection (ARI) remains one of the leading causes of morbidity and mortality among children under five, especially in developing countries. Exposure to cigarette smoke within the household environment is a major risk factor contributing to ARI incidence in toddlers. Parents’ smoking duration reflects long-term exposure that may increase susceptibility to respiratory infections in young children. High ARI cases reported at Bangetayu Health Center indicate the need to further investigate contributing household factors, including smoking duration. This study employed a quantitative analytic design with a cross-sectional approach. A total of 144 respondents were selected through purposive sampling. Smoking duration data were collected using a structured questionnaire, while ARI status was obtained from the MTBS (Integrated Management of Childhood Illness) records at the health center. Data were analyzed using the Chi-Square test to determine the relationship between variables. Most respondents were categorized as heavy smokers with a smoking duration of more than 10 years (76.4%). The majority of toddlers (85.4%) were recorded as having ARI. Statistical analysis revealed a significant relationship between parents’ smoking duration and ARI incidence (p = 0.031). Toddlers whose parents were heavy smokers had the highest proportion of ARI cases (88.2%). There is a significant correlation between parents’ smoking duration and the incidence of ARI among toddlers. Longer smoking duration increases the child’s risk of developing ARI.